Gender differences in gluteus medius muscle activity exist in soccer players performing a forward jump - Hart, J. A.; Garrison, C.; Kerrigan, D. C.; Palmieri-Smith, R.; Ingersoll, C. D. (Research in Sports Medicine, 2007)
The purpose of this study was to evaluate gender differences in muscle activity while landing from a forward jump. Eight male and 8 female division-one varsity soccer athletes participated in this study. Subjects performed five trials of a 100 cm forward jump single leg landing. Surface electromyography (EMG) was collected at the gluteus medius, vastus lateralis, lateral hamstring, and medial gastrocnemius. Data were interpreted by VICON workstation and analyzed with Acknowledge software. Average root mean square of 200 ms following initial heel contact from landing were normalized to static one-leg stance and used in data analysis. A fixed-effect multivariate analysis of variance showed average gluteus medius activity was significantly higher in males (7.16 ± 3.16) than in females (2.62 ± 0.95). There were no differences between genders for any of the other muscles collected. Gender-specific neuromuscular strategies used to attenuate the forces of landing may involve more gluteus medius muscle activity in males than in females.